2014
DOI: 10.1007/s12020-014-0433-5
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant murine fibroblast growth factor 21 ameliorates obesity-related inflammation in monosodium glutamate-induced obesity rats

Abstract: The aim of this study is to investigate the role of FGF21 in obesity-related inflammation in livers of monosodium glutamate (MSG)-induced obesity rats. The MSG rats were injected with recombinant murine fibroblast growth factor 21(FGF21) or equal volumes of vehicle. Metabolic parameters including body weight, Lee's index, food intake, visceral fat and liver weight, intraperitoneal glucose tolerance, glucose, and lipid levels were dynamically measured at specific time points. Liver function and routine blood te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 30 publications
5
40
0
Order By: Relevance
“…The administration of recombinant FGF21 to streptozotocin-treated mice dosedependently repressed FGF21 gene expression in the liver to a greater extent than streptozotocin alone [41]. In a separate study, FGF21 transcript levels were substantially lowered in the liver following FGF21 administration [42]. These results suggest the presence of a negative feedback by FGF21 directed at its own expression.…”
Section: Body Of Review Regulation By Starvation and Overnutritionmentioning
confidence: 83%
“…The administration of recombinant FGF21 to streptozotocin-treated mice dosedependently repressed FGF21 gene expression in the liver to a greater extent than streptozotocin alone [41]. In a separate study, FGF21 transcript levels were substantially lowered in the liver following FGF21 administration [42]. These results suggest the presence of a negative feedback by FGF21 directed at its own expression.…”
Section: Body Of Review Regulation By Starvation and Overnutritionmentioning
confidence: 83%
“…FGF21 is also secreted into circulation as a myokine in Cpt1b m−/− mice and promotes browning of inguinal white adipose tissue (iWAT), but not eWAT in Cpt1b m−/− mice24. Recent reports have shown that FGF21 decreased expression of IL6 and TNFα in adipose tissue of obese rats and suppressed inflammation in mouse models with FA-induced or diabetic renal dysfunction6465. Thus muscle derived FGF21 in Cpt1b m−/− mice could have anti-inflammatory action locally in the presence of intracellular toxic lipids, and on adipose or possibly other tissues by circulation contributing to the improvement in inflammatory status at the face of constantly elevated systemic lipids.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, rats treated with MSG at the neonatal period developed hypophagia, accompanied by arrest in the body weight gain, and concomitant enhanced basal levels of all HPA axis components and leptin (Perello et al 2003;Quines et al 2014). This longterm deregulation in the energy homeostasis induced several metabolic alterations (Poletto et al 2015;Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that MSG administration induces alterations in glucose transporters (GLUT) in the liver, muscle and fat and this is associated with hyperglycemia and insulin resistance present in these animals (Nardeli et al 2011;Leguisamo et al 2012;Poletto et al 2015;Wang et al 2015). Furthermore, the MSGtreated rats develop hepatic steatosis in adulthood and an increase in the activities of ATPase enzymes in the liver, accompanied by an increase in the state III of mitochondrial respiration (Lazarin et al 2011;Oliveira et al 2011;Wang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation